2003
DOI: 10.1128/mcb.23.24.9025-9031.2003
|View full text |Cite
|
Sign up to set email alerts
|

REST/NRSF-Interacting LIM Domain Protein, a Putative Nuclear Translocation Receptor

Abstract: The transcriptional repressor REST/NRSF (RE-1 silencing transcription factor/neuron-restrictive silencer factor) and the transcriptional regulator REST4 share an N-terminal zinc finger domain structure involved in nuclear targeting. Using this domain as bait in a yeast two-hybrid screen, a novel protein that contains three LIM domains, putative nuclear localization sequences, protein kinase A phosphorylation sites, and a CAAX prenylation motif was isolated. This protein, which is localized around the nucleus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 31 publications
(38 reference statements)
2
77
0
Order By: Relevance
“…Pk1b contains one PET domain, three LIM domains, three nuclear localization signals (NLSs) and a farnesylation motif (CaaX), as has been reported previously for other Pk homologs (Jenny et al, 2003;Shimojo and Hersh, 2003) (Fig. 1A).…”
Section: A Mutation In the Pk1b Farnesylation Motif Blocks Fbmn Migramentioning
confidence: 74%
See 4 more Smart Citations
“…Pk1b contains one PET domain, three LIM domains, three nuclear localization signals (NLSs) and a farnesylation motif (CaaX), as has been reported previously for other Pk homologs (Jenny et al, 2003;Shimojo and Hersh, 2003) (Fig. 1A).…”
Section: A Mutation In the Pk1b Farnesylation Motif Blocks Fbmn Migramentioning
confidence: 74%
“…Previous research has shown that human PK1 functions at the nuclear membrane to regulate nuclear translocation of the transcriptional silencer REST (Shimojo and Hersh, 2003;Shimojo and Hersh, 2006). We 2127 RESEARCH ARTICLE Pk1b farnesylation during FBMN migration hypothesized that this role is conserved in zebrafish Pk1b, and therefore first sought to determine whether REST functions during FBMN migration.…”
Section: Rest Function Is Required For Fbmn Migrationmentioning
confidence: 99%
See 3 more Smart Citations